Teknik pembuatan tepung tulang ikan tuna pada Kegiatan Pengabdian PPUPIK Rumah Ikan - Umar Tangke; Aisyah Bafagih; Ruslan A. Daeng (Universitas Negeri Makassar, 2020)
This fish bone waste is realized by the university as an important and potential material to be developed into something that is beneficial to the body because it contains various important substances for the needs of the human body including calcium, where calcium is an essential nutrient in various bodily functions, one of which as nutrients to grow and support the development of motor functions to be more optimal and develop well. The results of the activity obtained tuna bone waste after going through several processes and innovations, becoming a product that is beneficial to the body. As has been done in the PPUPIK House of fish activities where the waste that had been a source of pollution in both form and odor has become a useful product to increase the value of calcium and a good source of calcium to be added as a fortification ingredient in the processed products of PPUPIK Rumah Ikan namely tuna kering kayu and tuna rica-rica.